USE OF CLASS PROJECTS IN PEDAGOGICAL HIGHER EDUCATION AS A WAY OF DEVELOPING STUDENTS' CREATIVE ABILITIES (Pedagogy of Higher and Secondary Education, 2004)
The article investigates the problem of developing students creative abilities in terms of project work This type of the activity enables a teacher to solve not only the problem of student talking and better quantity and quality of the language used in class but developing students ’ creative abilities as well.